The Behavioral Inhibition System/Behavioral Activation System Scales: Measurement Invariance Across Gender in Chinese University Students - Xu, Ming; Wang, Jinyu; Jin, Zhishuai; Xia, Lu; Lian, Qiaoping; Huyang, Sizhu; Wu, Daxing (Frontiers in Psychology, 2021)
Objectives: To identify the optimal factor structure of the behavioral inhibition system/behavioral activation system (BIS/BAS) scales and to examine measurement invariance of the scales across gender among a sample of Chinese undergraduate students. Methods: Convenience sampling was employed to recruit 1,085 subjects. Participants completed the Chinese version of the BIS/BAS scales. A confirmatory factor analysis (CFA) of competing models was conducted to determine the optimal factor model, followed by a test of measurement invariance across gender based on the optimal model. Results: A single-group CFA indicated that the modified four-factor structure fit best in the total sample. Multiple-group CFAs demonstrated that configural invariance, weak invariance, strong invariance, and strict invariance models of the four-factor structure of the BIS/BAS scales were all acceptable. Conclusion: The four-factor structure of the Chinese version of the BIS/BAS scales possesses measurement invariance across gender.